Research and the choice of a course of study - Gavilán de Labourdette, Mirta Graciela (2000)
This paper presents some research on the choice of a course of study as related to a certain social, family and labor context. The methodology used included the definition of the theoretical basis and a series of empirical investigations which comprised different kinds of surveys, records, observations, participants as well as other fieldwork. The results obtained shed some light on the issue and raise new questions. This study was especially carried out to analyze the choice of the following courses of study: Law, Psychology and the different Teaching Courses.